MADURA POPULER: SUARA ANAK MUDA PULAU KAMBING - ardhie raditya (JURNAL SOSIAL Jurnal Penelitian Ilmu-Ilmu Sosial, 2021)
Abstract â€“ The islanders who are geographically separated from the mainland island of Madura have long been absent from the attention of popular culture. They tend to be considered alienated people and left behind from the high culture of the Madurese people. In fact, the popular culture brought and spread by the popular class of Madurese is a clue to their openness to the outside world or the development of the times. Madura's popular class consists of young people, either individuals or collectives, who are passionate about a variety of popular cultural products and practices. This research will be concentrated on the popular class in Kambing Island, Sampang regency, Madura. The research methods used collaborate between cultural studies and case study. The main data sources come from informal conversations, the experience of walking around the location, and participant observations with Kambing island youngsters. Based on field work analysis shows the pleasure of goat island young people towards popular culture refers to fandom or idolization culture, mobile phone use, and fashion style. The popular culture of the young people of Kambing Island is formed because of the political power of friendship and the rhythmic world of their everyday life.Â Â